Postoperative Urinary Leakage Following Partial Nephrectomy for Renal Mass: Risk Factors and a Proposed Algorithm for the Diagnosis and Management. (June 2017) - Erlich, T.; Abu-Ghanem, Y.; Ramon, J.; Mor, Y.; Rosenzweig, B.; Dotan, Z.
Objectives: To evaluate the current incidence, risk factors, management, and long-term follow-up of urinary leakage following partial nephrectomy, in order to propose an algorithm for diagnosis and evaluation of postoperative urinary leakage. Materials and Methods: The study included 752 patients who underwent elective partial nephrectomies for renal masses between the years 1988 and 2013. Patients' demographics, clinico-pathologic variables, and operative details were collected retrospectively. The associations between urinary leakage and patients' variables were assessed by univariate and multivariate analyses. Results: Of the 752 patients, 21 (2.8%) experienced urinary leakage; 4 of the 21 patients with urinary leakage had spontaneous resolution, 1 patient underwent nephrectomy, and 16 patients were treated by retrograde ureteral stents insertion. One of them necessitated insertion of an additional percutaneous nephrostomy and another one deserved concomitant percutaneous drainage of a perirenal urinoma. The average period of time that elapsed from the operation until the insertion of stent was 8.5 ± 4.5 days. Stents were removed 68 ± 20.5 days postoperatively. None of the patients had either persistent or repeated leakage. On univariate analysis, hilar renal masses (p < 0.04) and higher preoperative creatinine levels (p < 0.01) were found to be associated with higher rates of urinary leakage. None of these variables was significant on a multivariate analysis. Review of the urinary leakage rate over time revealed it has been constantly decreasing over time, from 4% in early cases to 1.3% among the most recent ones. Conclusion: None of the preoperative variables that were examined in this study was significantly associated with increased risk of urinary leakage. However, cumulative surgical experience was associated with lower rates of urinary leakage, suggesting that the decrease in its incidence is related to the improved surgical skills, rather than to differences in tumors' or patients' characteristics.